2016
DOI: 10.1016/j.revpalbo.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Pollen signals of ground flora in managed woodlands

Abstract: Please cite this article as: Bunting, M.J., Grant, M.J., Waller, M., Pollen signals of ground flora in managed woodlands, Review of Palaeobotany and Palynology (2015), doi: 10.1016/j.revpalbo.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Evidence for a strongly local component in the pollen signal comes from multiple investigations of modern pollen representation in wetland and grassland communities (e.g. Janssen, 1984;Hjelle, 1997;Bunting et al, 1998;Waller et al, 2005;Bunting et al, 2016) and from the fine scale heterogeneous mosaic nature of the vegetation deriving from the small size of individual plants and micro-scale variations in habitat (e.g. Bunting, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for a strongly local component in the pollen signal comes from multiple investigations of modern pollen representation in wetland and grassland communities (e.g. Janssen, 1984;Hjelle, 1997;Bunting et al, 1998;Waller et al, 2005;Bunting et al, 2016) and from the fine scale heterogeneous mosaic nature of the vegetation deriving from the small size of individual plants and micro-scale variations in habitat (e.g. Bunting, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…With any of the interrupted sites, it is important to note that the temporary decreases in the abundance of arboreal pollen could feasibly be driven by a period of active coppice management rather than a genuine woodland interruption. However, the impact of coppicing on pollen records in woodland settings has been considered by Waller et al, (2012) and Bunting et al, (2016) and concluded that coppicing has little or no impact on pollen production. We can thus be confident that periods interpreted as woodland interruptions are likely to be just are clearance events, even those that are very short (e.g.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Tauber traps allow the time period covered by the pollen assemblages to be defined accurately, although the requirement for a long-term continuous series of annually collected data to avoid problems of interannual variations in pollen production (Hicks, 2003) means that this approach is not feasible within the lifespan of many research projects. Bunting et al (2015) show that there may be a significant degree of local heterogeneity between closely spaced Tauber traps, indicating that micro-scale variation between pollen assemblages is not peculiar to those contained within moss polsters. Lake surface sediment samples are another option (e.g.…”
Section: Accepted M Manuscriptmentioning
confidence: 88%